Impulsivity: a link between bipolar disorder and substance abuse - Swann, Alan C; Dougherty, Donald M; Pazzaglia, Peggy J; Pham, Mary; Moeller, F Gerard (Bipolar disorders, 2004)
Background:  Substance abuse is present in most patients with bipolar disorder and associated with poor treatment outcome and increased risk of suicide. Increased impulsivity may be a link between bipolar disorder and substance abuse. Methods:  First, we compared impulsivity as a stable trait (Barratt Impulsiveness Scale, BIS) and as state‐dependent behavioral laboratory performance (Immediate Memory–Delayed Memory task, derived from the Continuous Performance Task) in interepisode bipolar and non‐bipolar subjects with and without substance abuse. Secondly, we compared impulsivity in interepisode and manic bipolar subjects with and without substance abuse. Results:  The BIS scores were increased in interepisode bipolar disorder and in subjects with histories of substance abuse, and were increased further in interepisode bipolar subjects with substance abuse. Performance impulsivity was increased in subjects with substance abuse, regardless of whether they had bipolar disorder. Among subjects with bipolar disorder, after correction for age, BIS scores were increased in those with substance abuse. Performance impulsivity was increased in manic compared with interepisode subjects, regardless of substance abuse history, and was increased in interepisode subjects with substance abuse similarly to manic subjects without substance abuse. These differences could not be accounted for by age, gender, or course of illness. Conclusions:  Trait impulsivity is increased additively in bipolar disorder and substance abuse. Performance impulsivity is increased in interepisode bipolar disorder only if a history of substance abuse is present. This increased predisposition to impulsivity when not manic may contribute to the decrement in treatment outcome and compliance, and increased risk for suicide and aggression, in bipolar disorder with substance abuse.